Screening and identification of HLA-A2-restricted neoepitopes for immunotherapy in endocrine therapy-resistant breast cancer - Mingshuang Wang; Liwei Pang; Yingjie Sun; Jingjing Han; Jiani Fan; Wenhui Shen; Xiaonan Hu; Bingqian Yang; Haoming Ning; Yanan Kong; Duo Li; Wenshan Zhao; et al. (Neoplasia: An International Journal for Oncology Research, 2025)
Endocrine therapy has shown significant clinical efficacy in estrogen receptor alpha (ERα)-positive breast cancer management, but the emergence of therapy-resistant mutations significantly undermines treatment outcomes, frequently leading to disease progression and metastasis. Among these resistance mechanisms, mutations in the ESR1 gene are particularly prevalent, detectable in 76% of endocrine therapy-resistant tumor specimens. The identification of immunogenic neoepitopes derived from mutant ESR1 offers a promising therapeutic avenue for patients with endocrine therapy-resistant breast cancer. In this study, we systematically investigated the mutational landscape of ESR1 across various cancer types, with particular emphasis on mutation frequency and spectrum analysis. Our findings revealed that non-synonymous ESR1 mutations predominantly occurred in breast cancer, clustering at four distinct hotspot sites: K303, E380, Y537 and D538. We further characterized the mutation prevalence at these hotspots across different breast cancer subtypes. Through comprehensive screening, we identified eight human leukocyte antigen (HLA)-A*0201 restricted immunogenic neoepitopes derived from ESR1 hotspot mutations. These neoepitopes demonstrated the capacity to elicit specific cytotoxic T lymphocytes (CTLs) responses both in vitro and in vivo. The induced CTLs exhibited specific recognition and cytotoxic activity against both T2A2 cells loaded with mutant neoepitopes and HLA-A*0201-positive breast cancer cells transfected with minigene encoding mutant neoepitopes. Notably, adoptive transfer of T cells primed with a peptide pool containing these eight neoepitopes significantly suppressed tumor growth and enhanced CD8+ T cells infiltration within tumor tissue. These findings suggest that the identified neoepitopes represent promising candidates for the development of tumor shared neoantigen vaccines.